Economic Valuation of Peatland Carbon Sequestration in Kebun Plasma Nutfah, Kedaton Village, Kayuagung District, South Sumatra Province - Olce Veronica; Eka Intan Kumala Putri; Dea Amanda; Nuva Nuva (Jurnal Ilmu Lingkungan, 2025)
Peatlands in Indonesia are currently experiencing deforestation and degradation caused by peatland fires. The peatland restoration policy that has been established aims to tackle peatland fires while preventing them from recurring. Peatland restoration is necessary because peatland fires contribute large emissions to the environment, impacting climate change. Kebun Plasma Nutfah located in Ogan Komering Ilir District, South Sumatra Province is one of the pilot projects to restore burnt peat swamp forests. Kebun Plasma Nutfah is a peat swamp forest that burned repeatedly in 1997 and 2006 during the dry season. Kebun Plasma Nutfah was then revegetated with commodities that are adaptive to peatlands. This study aimed to monetize Kebun Plasma Nutfah’s carbon sequestration and define it as the economic value of peat swamp forest with a Tier 2 accuracy. The calculation of the economic value of carbon sequestration was carried out on above-ground and below-ground carbon pools in the 10-hectare peatland in Kebun Plasma Nutfah. The results of this study show that Kebun Plasma Nutfah has a carbon sequestration of 121.606.27 tons, with an economic value of carbon sequestration of Rp 48.216.885.174. The larger the diameter of the tree, the greater the  that the tree can absorb, and the deeper the peat, the higher the carbon stock. Peatland is indeed a carbon stock, but it has the potential to become fuel during the dry season, resulting in large emissions when fires occur. The current condition of the Kebun Plasma Nutfah requires collaborative management to preserve the Kebun Plasma Nutfah and prevent activities that can cause damage to peatlands in Kebun Plasma Nutfah.